Building better organizations : how to fuel growth and lead in a digital era - Jules, Claudy (Berrett-Koehler Publishers, Inc., 2022)
"This essential playbook shows how companies can scale success by coupling digital strategies with an investment in the health of their organizations and the people within. To scale and grow, a company must get the organizational elements right. That begins with having the right strategy, the right leadership to drive it, and the right talent, culture, and organizational design to realize a company's potential. This is especially true in the AI era, where a company's most valuable assets are its people. To begin with, leaders must rethink their value creation strategies. To hone their organizational edge, leaders must prioritize their organization's health in seven vital areas: strategic direction, culture, leadership, talent, organizational design, EID (equity, inclusion, and diversity), and well-being. No matter what type or size of business, those essential conditions must be leveraged for increased value and growth. Put simply: organizational matters matter. To hone their digital edge, leaders must understand AI, as advances in technology allow leaders to build organizations that can compete and win in the future. Finally, an investor mindset will enable leaders to invest wisely in the technology (and leverage that tech) that sets their organizations apart"--